Measuring citizen participation in urban regeneration: a reflection on the construction of the participation index for the Bip/Zip programme in Lisbon - Falanga, Roberto (2019)
Citizen participation in policymaking has become a worldwide key reference for the design and implementation of urban regeneration. Despite the growing rate of participatory processes, little evidence or scientific debate has been fostered on their measurement and, broadly speaking, evaluation. While challenges in providing robust evaluations are related to the difficulties in providing common definitions of citizen participation in policymaking, the limited sharing of theories and evidence compromises a more comprehensive understanding of the socio-political phenomenon. The article contributes to this topic by discussing the conceptualisation and operationalisation of the participation index for the Bip/Zip programme. Since 2011, the programme has tackled socio-spatial inequalities in 67 priority areas of Lisbon by funding local partnerships composed of local associations, NGOs, and parish governments committed to engaging local communities in the development of their activities. The participation index will be formulated from the convergence of data collected through quantitative and qualitative methods on the constitution of partnerships, the implementation of initiatives, and the provision of public funding. The discussion provides critical reflection upon opportunities and challenges of the ongoing process from the academic and policy sides, which can positively stimulate future research on the topic.